Genetic diversity in human Fc receptor II for immunoglobulin G: Fc gamma receptor IIA ligand-binding polymorphism. - Reilly, A F (1994)
Fc gamma receptors, and in particular genetic variation in these receptors, are important in disorders of hose defense, immunohematologic disease, and systemic autoimmune diseases. We investigated the His-Arg (CAT/CGT) polymorphism at codon 131 of the Fc gamma receptor IIA gene, which influences ligand binding by the receptor. Previously, individuals had been classified phenotypically on the basis of differential binding of murine immunoglobulin G1, but the Fc gamma receptor IIA genotype distribution has not been reported. We used selective PCR-based sequence analysis of genomic DNA to determine the distribution in healthy individuals. For African-Americans, the genotype distribution was determined to be A/A (14%), A/G (60%), and G/G (26%); for Caucasian Americans, the distribution was A/A (30%), A/G (51%), and G/G (19%). These data correlate well with phenotypic data. We implemented a nonradioactive single-stranded conformational polymorphism analysis to rapidly identify all three genotypes. The PCR-single-stranded conformational polymorphism analysis method will facilitate studies of the genotype distribution in individuals with disorders of immune function.